The influence of the application of the snowball-throwing model based on local wisdom on the critical reasoning ability of elementary school students - Amaliya, Fadhia; Misbahudholam AR, Muhammad; Astuti, Yeni Puji (SAINTIS Publishing, 2024)
The purpose of this study is to determine the effect of the application of the Snowball-Throwing learning model based on local wisdom on the critical reasoning ability of grade IV students in science lessons at SDN Lalangon 1. The quantitative method was used in this study with a quasi-experimental design of a nonequivalent control group, which involved the experimental class and the control class. Simple random sampling was used to determine the control class and the experimental class, so that the control class was class IVA (23 students) and the experimental class was class IVB (22 students). Data collection techniques include interviews, tests, observations and documentation. The data were analyzed using descriptive data analysis, normality test, homogeneity, and independent T-test on normal data, and Mann-Whitney test on abnormal data with the help of SPSS-23. The results showed that the average post-test of the control class (65,217) was lower than that of the experimental class (77,841). The results of the independent T-test had a significance value of 0.024 ( 0.05), proving that the Snowball-Throwing model based on local wisdom had a significant effect on students' critical reasoning skills in the fourth-grade science lesson of SDN Lalangon 1. In addition, the average achievement of critical reasoning indicators in the experimental class (66%) was higher than that of the control class (44%). Thus, this learning model is not only effective in improving students' critical reasoning skills, but also introducing local wisdom of traditional Sumenep food in a meaningful way.